Pendataan Rumah Terdampak Pembangunan Jalur Jalan Lintas Selatan (JJLS) di Kabupaten Gunungkidul sebagai Penataan Permukiman - Yemima Sekar Arum Cahyaningtyas; Agustina Kiky Anggraini (Jurnal Atma Inovasia, 2026)
Gunungkidul Regency is part of a national strategic project aimed at strengthening connectivity across the southern coastal region of Java. The project is implemented by the Public Works Agency of Gunungkidul Regency in collaboration with private-sector teams and supported by academic experts from Atma Jaya Yogyakarta University. This infrastructure development directly affects residential areas along the planned road corridor. This community service initiative aims to map and document houses affected by the South Java Coastal Route (JJLS) construction as a basis for settlement planning by utilizing Google Earth satellite imagery as a simple mapping tool. The target of this data collection includes residents living along the JJLS alignment across four subdistricts: Girisubo, Tepus, Jerukwudel, and Rongkop. The methods include visual identification of affected houses using Google Earth imagery, measurement of distances from the JJLS corridor, field verification with local communities, and development of a database and distribution maps. The outputs include KMZ files containing coordinate points and house attributes, village-level distribution maps, and a spatial database for relocation planning and settlement arrangement. This initiative shows that Google Earth–based technology can be an effective and economical alternative for participatory spatial data collection in rural areas affected by infrastructure projects.